The practices of customer satisfaction survey among Malaysian libraries - Md Ishak, Amir Hussain; Sahak, Mohd Dasuki (Persatuan Pustakawan Malaysia, 2014)
This paper aims to identify the current practices of customer satisfaction survey (CSS) among Malaysian libraries. A self-developed questionnaire was used to gauge the respondents’ opinions on the implementation of CSS in their library. The questionnaire was distributed to 150 Malaysian libraries comprising samples of academic, public and special libraries. Descriptive and crosstabs statistics were used in the data analysis. The results of the study revealed that most libraries 1) start to implement CSS from year 2000 to 2010; 2) have applied CSS as a part of ISO requirement; 3) generally CSS is managed by Customer Services Division, 4) use Self Develop Instruments and study will be done on a yearly basis. The results also revealed that there are apparent lacks of CSS training and results distribution among the library staff. There are few suggestions on improving CSS such as forming focus group discussion, online survey, involve more respondents and create CSS standard among Malaysian library.